Analisis Gaya Mengajar Guru Dalam Pembelajaran Daring Pada Siswa Kelas IX B Di SMPN Manarai Nomor 18 Kepulauan Selayar - Ratna Deli (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2022)
This research was conducted at SMPN Manarai no 18 Kepulauan Selayar. The purpose of this study was to analyze Teacher's Teaching Style in online learning at SMPN Manarai no 18 Kepulauan Selayar. The type of research used was qualitative research. The subject in this study was the teacher. as for the data collection in this study are interviews and documentation. Test the validity of the data in this study is triangulation of sources.The results of this study are that when teaching online, Class IX B teachers have taught well, but because learning is carried out online, students sometimes become bored, Class XI B teachers also often provide motivation and use variations in styles when teaching online so that students become participative. but the activeness of the students is not clearly visible, and the variation in voice is also not clearly described because the learning process is carried out online and is limited, besides that the class IX B teacher uses a variety of media but there are still limitations of the media used during online learning. Class IX B teachers also give practical assignments to make paper flower crafts during online learning, and the teaching styles used by Class IX B teachers are demonstration teaching style, practice teaching style, and assignment teaching style